(untitled) (Bangladesh Heart Journal, 2021)
Beckground: This is often difficult to achieve optimal pain relief after coronary artery bypass surgery and also great challenge to choice appropriate analgesics with minimize the duration of mechanical ventilation. In the postoperative period inadequate analgesia may increase morbidity by causing adverse haemodynamic, metabolic, immunologic and haemostatic attentions and prolong mechanical ventilation with more ICU stay. High Thoracic Epidural Anaesthesia (HTEA) as an adjunct to general anaesthesia has been shown to be potentially beneficial in postoperative pain relief and the requirement of mechanical ventilationin patients with off-pump coronary artery bypass surgery (OPCAB). HTEA provides good protection from stress response, ensures hemodynamic stability, improves distribution of coronary blood flow with reducing demand of oxygen, less requirement of postoperative analgesia , mechanical ventilation and ICU stay. Objective: This study has been undertaken with a view to compare requirement of postoperative mechanical ventilation and analgesics in OPCAB surgery between HTEA with GA and GA alone. Methods: This prospective, randomized case control comparative study was carried out in sixty patients without having left main coronary artery disease, left ventricular ejection fraction <30% or contraindication of regional anaesthesia scheduled for OPCAB. They were divided into two groups, thirty in each group. Group A received GA alone and group B received high thoracic epidural anaesthesia with GA. Requirement of postoperative analgesics, pain score, consciousness score, sedation score, satisfection level and duration of ventilation with length of stay in intensive care unit were recorded in the post-operative period. Results: Rescue analgesics received and found 16(53.3%) and 6(20.0%) needed analgesia in group A and group B respectively and the difference was statistically significant (p<0.05). Regarding the pain score (VAS) during maintenance with ventilator with awareness at first fourth hour significant (p<0.05) change between two groups. After extubation at rest in different time interval and found significant (p<0.05) change between two groups in all follow-up times. Post-operative pain score (VAS) after extubation at movement in different time interval and found significant (p<0.05) change between two groups. Post-operative pain score (VAS) after extubation at during coughing in different time interval and found significant (p<0.05) change between two groups. Post-operative sedation score at first six hour (hourly) and found significant (p<0.05) change between two groups except 1st hour, which was not significant (p>0.05). The mean extubation hours were 7.4±1.09 hours in group A and 5.3±0.81 hours in group B. The mean ICU stay was 72.9±9.2 hours in group A and 57.1±12.0 hours in group B and the difference was statistically significant (p<0.05) in unpaired t-test. No postoperative complication was observed in both groups. Conclusion: HTEA with GA appeared to be most reliable postoperative pain relief, shorter mechanical ventilation, ICU stay in OPCAB surgery Bangladesh Heart Journal 2021; 36(2): 74-81